Green synthesis of eco-friendly bioplastics from Chlorella and Lithothamnion algae for safe and sustainable solutions for food packaging - Hussien Nahed Ahmed; Salah Al-Deen Maria Kamaluldeen; Al-zahrani Muzun Saeed; Alwathnani Shahad Fehaid; Al-Sahli Rana Yahya; Albunyusi Shatha Ruddah; Al-Humayani Shahad Salem; Alharthi Samar Salman; Almutairi Mathael Faleh; Algethami Fawz Fahad; Alqurashi Shouq Mohammed (Green Processing and Synthesis)
Global plastic waste production reaches approximately 400 million metric tons annually. Chemical plastics cause global pollution and take hundreds of years to degrade. Bioplastics are a promising alternative to traditional plastics made from renewable resources, such as plants and algae, and are biodegradable. The present study aims to synthesize eco-friendly bioplastics using green Chlorella and red Lithothamnion algae in addition to glycerol and starch as plasticizers. Moreover, the biosynthesized plastics were characterized using scanning electron microscopy, energy-dispersive X-ray spectroscopy (SEM/EDS), and Fourier transform infrared (FTIR) spectroscopy. In addition, we have checked their biodegradability on the soil surface and in drinking water. The results report the successful synthesis of bioplastics using green Chlorella and red Lithothamnion algae due to texture, flexibility, and shape. SEM images show an irregular surface due to ridges and grooves in the microstructure of the bioplastic films. EDX analysis shows large carbon and oxygen contents due to starch in bioplastic films. FTIR reports peaks were attributed to the –CO, –OH, and –CH groups. Biodegradability was proven as the bioplastic film lost nearly 70% of its biomass on the soil surface (at day 35) and sank in water (at day 34) tests. The present study describes an eco-friendly novel method mostly based on using algae, thereby providing a sustainable blend for the manufacturing of bioplastics for use in several applications, including food package and agriculture, as it is biodegradable.